Artificial intelligence transformations in geotechnics: progress, challenges and future enablers - Brian Sheil; Christos Anagnostopoulos; Róisín Buckley; Matteo Oryem Ciantia; Eky Febrianto; Jinlong Fu; Zhiwei Gao; Xueyu Geng; Bin Gong; Kevin Hanley; Pengpeng He; Kostas Kolomvatsos; et al. (Computers and Geotechnics, 2026)

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Mind the gap - The need to integrate novel plankton methods alongside ongoing long-term monitoring - Matthew M. Holland; Luis Felipe Artigas; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Dafne Eerkes-Medrano; Marie Johansen; David G. Johns; Margarita Machairopoulou; Sophie Pitois; James Scott; et al. (Ocean & Coastal Management, 2025)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Effects of marine diesel on microbial diversity and activity in high Arctic beach sediments - Margaux Durand; David Touchette; Ya-Jou Chen; Elisse Magnuson; Jessica Wasserscheid; Charles W. Greer; Lyle G. Whyte; Ianina Altshuler (Marine Pollution Bulletin, 2023)

Biodegradation potential of residue generated during the in-situ burning of oil in the marine environment - Ruby Pyke; Nathalie Fortin; Jessica Wasserscheid; Julien Tremblay; Lars Schreiber; Marie-Josee Levesque; Stephanie Messina-Pacheco; Lyle Whyte; Feiyue Wang; Kenneth Lee; David Cooper; Charles W. Greer (Journal of Hazardous Materials, 2023)

Neck Loads During Head-First Entries into Trampoline Dismount Foam Pits: Considerations for Trampoline Park Safety - Tom Whyte; Edward Lind; Adam Richards; David Eager; Lynne E. Bilston; Julie Brown (Annals of Biomedical Engineering, 2022)
Serious cervical spine injuries have been documented from falls into foam pits at trampoline parks. To address the lack of evidence on how foam pits should be designed for mitigating neck injury risk, this study aimed to quantify neck loads during head-first entry into varying foam pit designs. An instrumented Hybrid III anthropomorphic test device was dropped head-first from a height of up to 1.5 m into three differently constructed foam pits, each using a different mechanism to prevent direct contact between the falling person and the floor (foam slab, trampoline or net bed). Measured neck loads were compared to published injury reference values. In the simplest, foam-only pit design, increasing foam depth tended to reduce peak compressive force. At least one injury assessment reference metric was exceeded in all pit conditions tested for 1.5 m falls, most commonly the time-dependent neck compression criterion. The results highlight the importance of adequate foam depth in combination with appropriate pit design in minimizing injury risk. The risk of cervical spine injury may not be reduced sufficiently with current foam pit designs.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Towards Alternative Approaches for Coupling of a Soft Robotic Sleeve to the Heart - Markus A. Horvath; Claudia E. Varela; Eimear B. Dolan; William Whyte; David S. Monahan; Christopher J. Payne; Isaac A. Wamala; Nikolay V. Vasilyev; Frank A. Pigula; David J. Mooney; Conor J. Walsh; Garry P. Duffy; et al. (Annals of Biomedical Engineering, 2018)

The impact of chronic endurance and resistance training upon the right ventricular phenotype in male athletes - Victor Utomi; David Oxborough; Euan Ashley; Rachel Lord; Sarah Fletcher; Mike Stembridge; Rob Shave; Martin D. Hoffman; Greg Whyte; John Somauroo; Sanjay Sharma; Keith George (European Journal of Applied Physiology, 2015)

Erratum to: Herbiciding invasive reed: indirect effects on habitat conditions and snail–algal assemblages one year post-application - Christina L. Back; Joseph R. Holomuzki; David M. Klarer; Robert S. Whyte (Wetlands Ecology and Management, 2013)

Herbiciding invasive reed: indirect effects on habitat conditions and snail–algal assemblages one year post-application - Christina L. Back; Joseph R. Holomuzki; David M. Klarer; Robert S. Whyte (Wetlands Ecology and Management, 2012)

Left ventricular myocardial strain and strain rates in sub-endocardial and sub-epicardial layers before and after a marathon - Fang Chan-Dewar; David Oxborough; Rob Shave; Warren Gregson; Greg Whyte; Keith George (European Journal of Applied Physiology, 2010)

Evidence of increased electro-mechanical delay in the left and right ventricle after prolonged exercise - Fang Chan-Dewar; David Oxborough; Rob Shave; Warren Gregson; Greg Whyte; Tim Noakes; Keith George (European Journal of Applied Physiology, 2010)

Diastolic function in healthy humans: non-invasive assessment and the impact of acute and chronic exercise - Keith P. George; Louise H. Naylor; Greg P. Whyte; Rob E. Shave; David Oxborough; Daniel J. Green (European Journal of Applied Physiology, 2010)

Predicting breast cancer risk: implications of a “weak” family history - Elaine Anderson; Jonathan Berg; Roger Black; Nicola Bradshaw; Joyce Campbell; Roseanne Cetnarskyj; Sarah Drummond; Rosemarie Davidson; Jacqueline Dunlop; Alison Fordyce; Barbara Gibbons; David Goudie; et al. (Familial Cancer, 2008)

Analytical Solutions for Partitioned Diffusion in Laminates: I. Initial Value Problem with Steady Cauchy Conditions - Michael G. Trefry; David S. Whyte (Transport in Porous Media, 1999)

Distribution of the floating-leaf macrophyteNelumbo lutea (American water lotus) in a coastal wetland on Lake Erie - Robert S. Whyte; David A. Francko; David M. Klarer (Wetlands, 1997)